Java and XML - McLaughlin, Brett (Java series (O'Reilly & Associates), 2000)
XML has been the biggest buzzword on the Internet community for the past year. But how do you cut through all the hype and actually put it to work? Java revolutionized the programming world by providing a platform-independent programming language. XML takes the revolution a step further with a platform-independent language for interchanging data. Java and XML share many features that are ideal for building web-based enterprise applications, such as platform-independence, extensibility, reusability, and global language (Unicode) support, and both are based on industry standards. Together Java and XML allow enterprises to simplify and lower costs of information sharing and data exchange. Java and XML shows how to put the two together, building real-world applications in which both the code and the data are truly portable. This book covers: The basics of XML Using standard Java APIs to parse XML Designing new document types using DTDs and Schemas Writing programs that generate XML data Transforming XML into different forms using XSL transformations (XSL/T) XML-RPC Using a web publishing framework like Apache-Cocoon This is the first book to cover the most recent versions of the DOM specification (DOM 2), the SAX API (SAX 2) and Sun's Java API for XML.